Qualitative Chemical Analysis of Amalgamation of Mercury and Sulphur (Kajjali) in the Metallic Preparations Of Siddha Drugs - Thillany, P.V.; Sathiyaseelan, V.; Velauthamurty, K. (World Journal of Pharmaceutical Research, 2020)
Mercury is one of the extensively used metal in the preparations of siddha medicine after purification process. Amalgamation of purified mercury and purified sulphur is called Kajjali. Current issue has raised causing doubtful condition in using certain Siddha drugs that contains metallic raw materials, hence purification of them is very essential in order to avoid the side effects of the drugs. So the objective of the study is to identify the chemical state of mercury and sulphur after purification and in formation of amalgam (Kajjali) of both. For this, an experimental qualitative chemical analysis was conducted in the Department of Chemistry, University of Jaffna, Sri Lanka. After proper purification of both mercury and sulphur according to siddha literature, the amalgamation was made by combining them in the pharmacy, Unit of Siddha Medicine, University of Jaffna, Sri Lanka. Qualitative analysis was done with suitable reagents. As per to the observations, the relevant data's regarding the precipitations collected and justified. Results of the qualitative analysis suggested that each purified mercury and purified sulphur contains inorganic precipitations of certain substances and the amalgamation (kajjali) also contains both the combination of them. The findings indicated that purification of mercury and sulphur in amalgamation (kajjali) resulted in obtaining a chemical change from the base substances into inorganic forms of them which are nontoxic, to be used in medical preparations and industrial purposes. Apart from this, poor quality drugs which are of inappropriately detoxified raw materials can produce major illnesses. This is a vast problem arising from unauthorized dealers or persons who did not have qualified siddha medicine degree.
Keywords: Siddha; Amalgamation; Mercury; Qualitative; Inorganic